Plant microbiomes as contributors to agricultural terroir - Johnston-Monje, David; Vergara, Laura Isabella; Lopez-Mejia, Jessica; White, James Francis (Frontiers in Agronomy, 2023)
Agricultural products such as tea, chocolate, coffee and wine are valued for their sensorial and nutritional qualities. Variation in the growing conditions of a crop can influence the plant’s phenotype, thus it behooves agriculturalists to optimize the conditions on their farms to grow the highest quality product. The set of growing conditions associated with a certain geographic location and its influence on the product’s chemistry is known as terroir. Although terroir plays a significant role in marketing and consumer appreciation as well as product identity and valorization, rarely are the biochemical differences or the factors creating them very well understood. The word derives from the Latin for “land”, suggesting terroir is simply a function of the geographical location where a plant grew, while in its modern usage, terroir is the result of soil type, climate, landscape, topography, biotic interactions and agricultural practice. Except for fermented food products like wine and chocolate, plant associated microbiomes have been little studied for their contribution to a crop’s terroir; however, modern metagenomics and metabolomics technologies have given scientists the tools to better observe how microbial diversity can impact the chemical variation in plant products. Differences in the microbiomes inhabiting plant organs can change phytochemistry by altering host metabolism, for example increasing the nutrients absorbed by roots that then are deposited in leaves, seeds and fruits. Plant associated microbes can consume plant molecules, removing them from the metabolome, or they can contribute smells and flavors of their own. This review aims to synthesize research into rhizosphere, endosphere, phyllosphere, spermosphere, carposphere, and anthosphere microbiome influences on plant biochemistry and crop derived products, while helping to increase the appreciation that beneficial microbes are able to contribute to agriculture by improving phytochemical quality.